PCOS is Associated with Atherogenic Changes in Lipoprotein Particle Number and Size Independent of Body Weight - Sidhwani, Seema (2011)
OBJECTIVE: Adverse changes in lipoprotein particle number and size are common with insulin resistance and are associated with increased cardiovascular risk. Comprehensive information regarding lipoprotein particle number and size, and how these parameters relate to body weight, insulin resistance and hyperandrogenemia is lacking in PCOS. We tested the hypothesis that PCOS is associated with atherogenic changes in lipoprotein profile independent of body weight and examined the role of insulin resistance and androgens in these atherogenic changes. DESIGN: Case-control study performed at Clinical Research Center at an Academic Medical Center in United States. PATIENTS AND MEASUREMENTS: Fasting Blood was obtained from 25 PCOS and 25 control women of similar age and BMI. Lipoprotein particle number and size was determined by nuclear magnetic resonance and compared between the groups. RESULTS: The mean BMI for both groups was less than 30 kg/m(2) (P=0.33). Women with PCOS had an increase in VLDL particle number (P=0.005), LDL particle number (P=0.02) and a decrease in HDL size (P=0.04). LDL size was borderline decreased (P=0.09). These differences persisted after adjustment for ethnicity, alcohol and tobacco intake and exercise. In stepwise regression models, bioavailable testosterone was the only predictor of LDL cholesterol, triglyceride, VLDL and LDL particle number. SHBG was the only predictor of LDL and HDL size. CONCLUSIONS: Independent of body weight, PCOS was associated with changes in lipoprotein profile that increases risk for cardiovascular disease. These changes were present in a mostly non-obese group of women and were more closely related to androgens than fasting insulin.